(untitled) (Sains Humanika, 2018)
Review of literature shows that empirical research on vocational intelligence (VQ) is lacking as compared to substantial research conducted on intellectual intelligence (IQ and emotional intelligence (EQ). Vocational intelligence is a new theory. It could be an offshoot from Howard Gardner’s multiple intelligence theory. The main objective of this investigation was to determine the vocational intelligence of technical school apprentices in the state of Perak, Malaysia. Gardner and Holland theories have been chosen as the basis for the study’s conceptual framework that contained six domains of vocational intelligence, namely realistic and artistic intelligence, artistic and realistic tendencies, and kinesthetic and visual talents. Multiple cases and multiple sites case study was selected as the study’s research design. A random sample of 306 vocational students was selected from four technical secondary institutions in Perak. Research instrument comprised questionnaire and interview questions to gather quantitative and qualitative information. Key finding from the questionnaire is that the technical secondary students believe that they possess the three main competencies ─ visual, kinesthetic, and artistic. The result also shows that background aspects of the students did not influence their VQ except the schoolings of the father and mother. In terms of the relationships among constructs, Pearson correlation coefficients show strong correlations among artistic competence with artistic tendency and realistic competence with realistic tendency. In contrast to questionnaire data, open-ended results show the technical school students believed that they are dominantly realistic, followed by artistic and visual. Interview data via thematic analyses show that students admitted that they have realistic VQ.